Gandhi's ascetic activism : renunciation and social action - Howard, Veena R. (State University of New York Press, 2013)
In this book, the author discusses Gandhi's creative use of ascetic practice, particularly his practice of celibacy, for nonviolent activism.
Keywords: Gandhi, -- Mahatma, -- 1869-1948 -- Philosophy.; Gandhi, -- Mahatma, -- 1869-1948 -- Religion.; Gandhi, -- Mahatma, -- 1869-1948; Asceticism -- Hinduism.; Celibacy -- Religious aspects -- Hinduism.; Passive resistance.; Nonviolence.; Ascétisme -- Hindouisme.; Résistance passive.; Non-violence.; RELIGION -- Hinduism -- General.; Asceticism -- Hinduism; Nonviolence; Passive resistance; Philosophy; Religion